IgM- and IgA-response of peritoneal B-1 cells to the TI-2 antigen with the presence of γδT cells in vitro - N. A. Snegireva; E. V. Sidorova; I. N. Dyakov; M. V. Gavrilova; I. N. Chernyshova; E. P. Pashkov; O. A. Svitich (Медицинская иммунология)
IgA is an important component of the mucosal system of the body. It limits penetration of pathogens into the bloodstream. Inflammatory diseases such as Crohn disease and colitis may be associated with disorders of IgA synthesis. Both B1 and B2 cells are a source of IgA in the intestines. Special attention is paid to B1 cells, which are able to respond to T-independent type 2 antigens and produce natural antibodies. B1 cells produce about 50% of the intestinal IgA including specific antibodies to the components of microorganisms contained in the gastrointestinal tract. The mechanism of IgA formation in the T-independent way is not investigated in details. It was suggested that the γδТ-cells promote switching to IgA synthesis by B1 cells. This assumption may be supported by their co-localization with B1 lymphocytes in the intestinal mucosa, as well as participation, along with B1 cells, in formation of the first-line defense against the pathogens. In addition, the both lymphocyte subpopulations evolve during initial ontogenesis, earlier than “classic” В2 and αβT cells. Therefore, it was suggested that γδT lymphocytes may be involved into the processes of induction and/or regulation of IgM and IgA production by B1 cells in response to TH2 antigens.In the present study, we have shown the effect of γδT cells upon generation of IgM- and IgA-forming B1 cells in response to α-1,3-dextran in vitro. We also studied the dynamics of the mRNA expression for IgM- and IgA-heavy chains by the B1 cells at different terms of in vitro culture.It was found that, during co-cultivation of B1 cells with 20% γδT lymphocytes, there is no increase in the number of dextran-specific IgM-producing cells. The B1 cells exhibited an increase of IgM heavy chain mRNA expression in response to dextran but not in co-cultures. Expression of mRNA for IgM heavy chains in co-cultures was decreased compared to non-treated B-cell cultures. Contrary to the earlier assumption, a presence of γδT lymphocytes in culture did not enhance the formation of IgA producents. The obtained data suggest regulatory properties of the γδТ lymphocytes during the B1 cells response to T-independent antigens.